Computational Model of the Cochlea using Resonance Analysis - Jiménez Hernández, Mario; Oropeza-Rodríguez, J L; Suarez Guerra, S; Barrón-Fernández, R (Revista Mexicana de Ingenieria Biomedica, 2012)
This paper presents the development of a computational model of the cochlea using a new solution by resonance analysis to the models of fluid mechanics in the cochlea and the basilar membrane as a system of forced harmonic oscillators proposed by Lesser and Berkeley. The computational model of resonance analysis is successfully compared with the method of numerical integration developed by Peterson and Bogert, the method of Green function proposed by Allen, the method of finite difference described by Neely and the measurements obtained in the experiments of Békésy, getting the same results with the new solution developed. Its contribution regarding the different solutions already found in the literature is to obtain a frequency-distance function to identify the maximum amplitude of displacement of each section along the basilar membrane for each specific excitation frequency in the hearing system. The model developed presents the advantage over the previous solutions, that the function obtained depends only of the physical characteristics of mass per unit area, damping coefficient and stiffness per unit area along the basilar membrane, and is the first time that the resonance analysis is used to obtain a methodology consistent with the place theory of hearing of Békésy.